Economics of Cultivation of some Commercially Important Medicinal Plants - Gera, Mohit; Gusain, M. S.; Ansari, M. Y.; Bisht, N. S. (Indian Forester, 2005)
Agro technologies for cultivation of a number of medicinal plant species have been developed but large-scale cultivation on farmlands is yet to begin. Amongst other causes for this gap, lack of reasonably correct information on economics of cultivation of these species is one important cause. The economics of cultivation of five medicinal plant species, viz., Kalmegh, Buch, Safed musli, Ashwagandha and Akarkara was studied on farmer's field in Haryana. The net benefits calculated for each species were also subjected to sensitivity analysis in relation to fall in price by 25%, 50%, 75% increase in wage rate by 10%, 20%, 30% and increase in rental value of land by 20%, 40% & 60%. The results showed that maximum net benefits of Rs 36,140 and Rs. 19,016 per acre could be received by cultivation of Safed musli and Kalmegh respectively. The cultivation of Kalmegh and Ashwagandha were observed to be more resilient to the adverse factors of price fall, increase in wage rate and rental value of land, compared to other species. On the basis of initial investment involved and resilience to adverse market conditions, the cultivation of Kalmegh and Ashwagandha is recommended for small farmers. The large farmers who can afford greater risk may cultivate Buch and Safed musli and Akarkara for higher returns.